Evaluation of NSPRI Solar Dryers for Yam Chips Production (Elubo) - Ogunsua, J. M.; Akomolafe, O. P.; Oyewole, S. N.; Ajiboye, O.; Zubair, M. O.; Idris, Y. D.; Omopariola, F. M.; Adeiza, O. A.; Olayemi, F. F. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study evaluated the two solar dryers developed at Nigerian Stored Products Research Institute (NSPRI) - Parabolic Shaped Solar Dryer (PSSD) and Solar Tent Dryer (STD). The evaluation was conducted using yam chips (Elubo) in Ilorin. The yam chip was soaked in water at three different temperatures: 80, 90 and 100°C, and allowed to cool in the water for 15 hours prior to drying. The yam samples were then spread on trays in each of the PSSD, STD dryers and Ambient. A TEKCOPLUS THTK-6, K- Type 4-channel thermocouple was fitted in each of the dryers to monitor the drying temperature inside the dryers and ambient. The study considered sun drying as the control. The product samples were subjected to proximate composition determination. The moisture content of the samples was also monitored daily. Means of data collected were compared using graphs and 2-way ANOVA using Microsoft Excel 2016 and SPSS version 20. The results showed higher temperatures recorded in the dryers (PSSD= 40.77 ± 1.24°C and STD= 34.62 ± 0.70°C) compared to what was obtained in the ambient (33.59 ± 0.38°C). This resulted in a higher drying rate in PSSD and STD at an average of 0.57 kg/day and 0.52 kg/day respectively compared to the control (0.46 kg/day). Drying in PSSD was completed in 3 days with final moisture content of 7.53%, while it lasted for 4 days in STD and Control with final moisture contents of 8.98% and 9.37% respectively. Similarly, carbohydrate and crude protein were found to be significantly higher in samples dried in PSSD compared to STD and the Controlled samples (P≤0.05). The result of microbial quality evaluation revealed that the bacteria and fungi counts of the dried yam chip samples inside PSSD and STD were within the acceptable standard of ≤ 300 Cfu/ml, lower than that of the control sample where higher value (1.80 x 103 Cfu/ml) was recorded. Therefore, both PSSD and STD are potentially viable for safe production of yam chips of high quality for human consumption.